2023
DOI: 10.3390/ijms24021228
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid/Multinucleated Giant and Slow-Cycling Cancer Cell Enrichment in Response to X-ray Irradiation of Human Glioblastoma Multiforme Cells Differing in Radioresistance and TP53/PTEN Status

Abstract: Radioresistance compromises the efficacy of radiotherapy for glioblastoma multiforme (GBM), the most devastating and common brain tumor. The present study investigated the relationship between radiation tolerance and formation of polyploid/multinucleated giant (PGCC/MGCC) and quiescent/senescent slow-cycling cancer cells in human U-87, LN-229, and U-251 cell lines differing in TP53/PTEN status and radioresistance. We found significant enrichment in MGCC populations of U-87 and LN-229 cell lines, and generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…The G Alert , spG0, G0 states in quiescence-and/or senescence-like may be an adaptive response of PGCCs to radiation stress. 127,128 Mallin et al 12 showed that PACC (PGCCs) exhibit increased motility and deformability mediated by increased mesenchymal-related protein expression, and that PACC show increased metastatic potential. PGCCs have thicker and longer actin fibres with an abnormal overexpression of actin components compared with the diploid cancer cells, which confers PGCCs a slow yet persistent migratory phenotype.…”
Section: Pgccs Have the Properties Of Dormant Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…The G Alert , spG0, G0 states in quiescence-and/or senescence-like may be an adaptive response of PGCCs to radiation stress. 127,128 Mallin et al 12 showed that PACC (PGCCs) exhibit increased motility and deformability mediated by increased mesenchymal-related protein expression, and that PACC show increased metastatic potential. PGCCs have thicker and longer actin fibres with an abnormal overexpression of actin components compared with the diploid cancer cells, which confers PGCCs a slow yet persistent migratory phenotype.…”
Section: Pgccs Have the Properties Of Dormant Cancer Cellsmentioning
confidence: 99%
“…Severe DNA damage from chemotherapy or hypoxia induces P53 up-regulation and cells with mutant P53 become aneuploid. 127 Endoreduplication increases the cell size, DNA content and nuclear heterogeneity in response to various stressors. 144,145 In PGCCs, CDK1 and cyclin B1 expression is down-regulated, whereas the expression of P53 is up-regulated.…”
Section: Pgccs Achieve Dormancy Through Endoreplicative Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, interaction with white blood cells also correlates with mixed Epithelial-mesenchymal phenotype and cancer cells polyploidy ( 21 , 68 , 69 ) that play a key role in cancer resistance to treatment and metastasis ( 37 , 70 72 ).…”
Section: Polyploidy and Epithelial-to-mesenchymal Transition In Ctc C...mentioning
confidence: 99%